Pengaruh Work-life Balance dan Work Stress terhadap Turnover Intention dengan Job Satisfaction sebagai Variabel Mediasi pada Karyawan Kontrak BP Batam - Mualifah Nurhidayati; Yuli Indah Fajar Dini (Jurnal Madani: Ilmu Pengetahuan, Teknologi, dan Humaniora, 2023)
The purpose of this study is to determine the effect of Work-life Balance and Work Stress on Turnover Intention with Job Satisfaction as a mediating variable in BP Batam contract employees. This research uses quantitative methods by distributing questionnaires. The total sample collected was 320 contract employees of BP Batam. Testing of the collected data is processed using Smart-Pls. Data analysis used in the form of validity, reliability, direct effect, indirect effect and determination coefficient test (R2). The results of this study indicate that work-life balance is significantly negative by turnover intention as seen from the sample mean of -0.253, t-statistic 4.171, P-value 0.000. Testing by work stress variables is significantly positive towards turnover intention with a sample mean of 0.240, t-statistic 3.122, P-value 0.002. There are positive significant test results by work-life balance on job satisfaction from sample mean 0.379, t-statistic 4.637, P-value 0.000. Work stress is negatively significant by job satisfaction as shown by the sample mean -0.260, t-statistic 3.878, and P-value 0.000. Job satisfaction is negatively significant to turnover intention at a sample mean of -0.171, t-statistic of 2.808 and P-value of 0.005. Testing the significant negative effect of work-life balance on turnover intention through the job satisfaction variable of sample mean -0.065, t-statistic 2.294, P-value 0.022. Testing the significant positive effect by the job satisfaction variable in mediating the relationship between work stress and turnover intention can be seen in the sample mean of 0.044, t-statistic 2.312, P-value 0.021. Abstrak Tujuan penelitian ini guna mengetahui pengaruh work-life balance dan work stress terhadap turnover intention dengan job satisfaction sebagai variabel mediasi pada karyawan kontrak BP Batam. Penelitian ini menggunakan metode kuantitatif dengan membagikan kuesioner. Total sampel yang terkumpul 320 karyawan kontrak BP Batam. Pengujian data yang terkumpul diolah dengan menggunakan Smart-Pls. Analisis data yang digunakan berupa uji validitas, reliabilitas, uji koefesien determinasi (R2), direct effect, indirect effect. Hasil penelitian ini menunjukkan bahwa work-life balance signifikan negatif oleh turnover intention yang dilihat dari nilai sample mean -0,253, t-statistik 4,171, P-value 0,000. Pengujian oleh variabel work stress signifikan positif terhadap turnover intention dengan nilai sample mean 0,240, t-statistik 3,122, P-value 0,002. Terdapat hasil pengujian signifikan positif oleh work-life balance terhadap job satisfaction dari sample mean 0,379, t-statistik 4,637, P-value 0,000. Work stress signifikan negatif oleh job satisfaction ditunjukkan dari sample mean -0,260, t-statistik 3,878, dan P-value 0,000. Job satisfaction signifikan negatif terhadap turnover intention pada nilai sample mean -0,171, t-statistik 2,808 dan P-value 0,005. Pengujian pengaruh secara signifikan negatif work-life balance terhadap turnover intention yang dilalui variabel job satisfaction dari sample mean -0,065, t-statistik 2,294, P-value 0,022. Pengujian pengaruh secara signifikan positif oleh variabel job satisfaction dalam memediasi hubungan antara work stress dengan turnover intention dapat dilihat pada sample mean 0,044, t-statistik 2,312, P-value 0,021. Kata Kunci: Work-life Balance, Work Stress, Turnover Intention